CONCEPTUAL FOUNDATIONS OF ACCOUNTING AND COSTING IN FRUIT AND VEGETABLE PROCESSING ENTERPRISES (International Congress on Economics, Management and Business Studies, 2026)
This study analyzes the conceptual foundations of accounting and costing at fruit and vegetable processing enterprises. The study highlights the issues of accounting for the stages of raw material acceptance, initial preparation, technological processing, packaging, storage and sales in a single information contour under the conditions of biological and seasonal characteristics. In the formation of accounting policies, the principle of the primacy of content over form, assessment based on quality indicators, the separation of normal and excess losses, and the recognition of secondary products are scientifically substantiated. Also, the impact of cost management, revenue recognition, internal control and audit mechanisms on economic efficiency, in combination with process and custom calculation elements, is analyzed. The results of the study serve to draw practical conclusions on improving accounting and management reporting at processing enterprises.
Keywords: Fruit and vegetable processing, accounting, cost reporting, value chain, process costing, normal and excess losses, inventory accounting, accounting policy, internal control, management accounting.